(untitled) (Canadian Medical Education Journal, 2019)
In this paper, we describe our efforts to improve resident understanding of Competency-Based Medical Education (CBME) in an Internal Medicine residency program that launched CBME earlier than most of the country’s programs. We also share the resources we have developed to address this issue with the intent of helping other programs have a successful launch.